Exploring Bottom-Up Visual Processing and Visual Hallucinations in Parkinson's Disease With Dementia - Murphy, Nicholas; Killen, Alison; Gupta, Rajnish Kumar; Graziadio, Sara; Rochester, Lynn; Firbank, Michael; Baker, Mark R.; Allan, Charlotte; Collerton, Daniel; Taylor, John-Paul; Urwyler, Prabitha (Frontiers in Neurology, 2021)
Visual hallucinations (VH) are a common symptom of Parkinson’s disease with dementia (PDD), affecting up to 65% of cases. Integrative models of their etiology posit that a decline in executive control of the visuo-perceptual system is a primary mechanism of VH generation. The role of bottom-up processing in the manifestation of VH in this condition is still not clear although visual evoked potential (VEP) differences have been associated with VH at an earlier stage of PD. Here we compared the amplitude and latency of pattern reversal VEPs in healthy controls (n=21) and PDD patients (n = 34) with a range of VH severities. PDD patients showed increased N2 latency relative to controls, but no significant differences in VEP measures were found for patients reporting complex VH (CVH) (n=17) compared to those without VH. Our VEP findings support previous reports of declining visual system physiology in PDD and some evidence of visual system differences between patients with and without VH. However, we did not replicate previous findings of a major relationship between the integrity of the visual pathway and VH.